Evaluating the Islamic Religious Education Program in Inclusive Early Childhood Education - Rita Sriayu; Siti Kamilah; Suherman Suherman; Zurqoni Zurqoni; Heri Retnawati (JUMPA : Jurnal Manajemen Pendidikan, 2025)
Islamic Religious Education (IRE) plays an important role in fostering religious awareness, moral development, and social character during early childhood. The implementation of IRE in inclusive Early Childhood Education (ECE), however, continues to face challenges related to teacher readiness, adaptive learning practices, and the evaluation of learning outcomes for children with diverse developmental characteristics. This study aimed to evaluate the implementation of the IRE program in inclusive ECE institutions in Balikpapan City using the Context, Input, Process, and Product (CIPP) evaluation model. A qualitative evaluative approach was employed. Data were collected through observations, in-depth interviews, and documentation involving school principals, classroom teachers, special needs assistant teachers, and educational supervisors. Data analysis followed an interactive process consisting of data reduction, data display, and conclusion drawing. The findings reveal that inclusive IRE practices have developed positively despite the absence of formal local regulations governing inclusive ECE. Significant challenges remain in teacher competencies, adaptive assessment practices, and the limited availability of special needs assistant teachers. Learning activities grounded in play, habituation, storytelling, emotional engagement, and direct religious practice were found to support the internalization of religious values and the development of children's social behavior. The evaluation further indicates that learning implementation remains highly dependent on individual teacher initiatives and lacks a structured conceptual framework for inclusive IRE. These findings highlight the need to strengthen teacher capacity in inclusive pedagogy, develop more adaptive and holistic assessment systems, and formulate an inclusive IRE model that integrates Islamic educational values, child-centered learning, and neurodiversity perspectives. The study contributes to the advancement of inclusive Islamic education by providing empirical evidence for the development of more equitable, adaptive, and humanistic learning environments in early childhood settings.